2023
DOI: 10.1186/s12933-023-01824-5
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of hypoxia-inducible factor 1α in the sympathetic nervous system accelerates diabetic cardiomyopathy

Abstract: Background An altered sympathetic nervous system is implicated in many cardiac pathologies, ranging from sudden infant death syndrome to common diseases of adulthood such as hypertension, myocardial ischemia, cardiac arrhythmias, myocardial infarction, and heart failure. Although the mechanisms responsible for disruption of this well-organized system are the subject of intensive investigations, the exact processes controlling the cardiac sympathetic nervous system are still not fully understood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 106 publications
0
4
0
Order By: Relevance
“…HIF1A is an important transcription factor that plays a key role in the adaptive response of cells to low-oxygen environments. It is found that abnormal expression of HIF1A in the sympathetic nervous system affects myocardial collagen deposition, ECM formation, and myocardial fibrosis in diabetic cardiomyopathy [ 50 ]. HIF1A has been shown to enhance the activation of cardiac fibroblasts by upregulating the expression of specific genes associated with ECM formation [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…HIF1A is an important transcription factor that plays a key role in the adaptive response of cells to low-oxygen environments. It is found that abnormal expression of HIF1A in the sympathetic nervous system affects myocardial collagen deposition, ECM formation, and myocardial fibrosis in diabetic cardiomyopathy [ 50 ]. HIF1A has been shown to enhance the activation of cardiac fibroblasts by upregulating the expression of specific genes associated with ECM formation [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the macro-level, HIF-1α plays a pivotal role in enhancing the myocardial tissue's tolerance to ischemic injury [ 8 ]. Diabetic mice deficient in HIF-1α exhibit significant cardiac contractile dysfunction, increased cardiac sympathetic innervation, and subsequent myocardial structural remodeling [ 38 ]. The expression of HIF-1α in myeloid cells provides protection during ischemia and reperfusion injury in the heart [ 39 ].…”
Section: Hypoxia-induced Modulation Of Hif-1α In Sepsismentioning
confidence: 99%
“…Plates were frozen immediately on dry ice and stored at −80°C. The total time from euthanasia to cell collection was ∼3 h. The RNA library preparation, RNA sequencing (RNA-seq), and data processing were performed as described previously (27). Briefly, the NEBNext single-cell low-input RNA library prep kit for Illumina (#E6420, New England Biolabs) was used for library generation at the Gene Core Facility (Institute of Biotechnology CAS, Czechia), and the libraries were sequenced on an Illumina NextSeq 500 next-generation sequencer with NextSeq 500/550 High Output kit 75 cycles (Illumina #200024906) at the Genomics and Bioinformatics Core Facility (Institute of Molecular Genetics CAS, Czechia).…”
Section: Rna Sequencing Of Fluorescenceactivated Cell-sorted Sympathe...mentioning
confidence: 99%
“…Changes in cardiac sympathetic innervation and sympathetic system activity are implicated in many pathologies in adults, including sudden cardiac death, myocardial ischemia, cardiac death, hypertension, diabetic heart disease, and heart failure ( 25 , 26 ). Emerging evidence suggests that many of the sympathetic dysfunctions in various pathological heart conditions have a developmental origin ( 19 , 20 , 27 , 28 ). Using conditional deletion of oxygen-sensitive subunit HIF-1α, we previously revealed a key role for the transcription factor hypoxia-inducible factor 1 (HIF-1) in the development of sympathetic neurons and sympathetic innervation of the developing heart and its negative effects on heart function in adults ( 29 ).…”
Section: Introductionmentioning
confidence: 99%